Marketing as a Strategic Tool in Veterinary Clinics of Small Animals - Soares, Jose Antonio; Galvao, Andre Luiz Baptista [UNESP]; Bresciani, Katia Denise Saraiva [UNESP] (My University, 2015)
This survey was conducted from October 2012 to July 2013 in orderto highlight the role of marketing as a strategic tool used to leverage business in the veterinary field that can make a difference in customer loyalty. Good services in this segment strengthen the image of both the professional and the company in such a competitive market nowadays. Initial service, technical support, and post customer service strengthen the bond of client-service provider that forms lasting partnerships and disseminates free of charge, through word of mouth, the activities offered and the way they are provided when the quality is good and exceeds expectations of customers.
Keywords: Entrepreneurship; Small business marketing; Veterinary marketing